2019
DOI: 10.1016/s2213-2600(18)30334-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term developmental effects of withholding parenteral nutrition for 1 week in the paediatric intensive care unit: a 2-year follow-up of the PEPaNIC international, randomised, controlled trial

Abstract: European Research Council Advanced Grant, Methusalem programme provided by the Flemish Government, Flemish Agency for Innovation by Science and Technology (IWT), Research Foundation Flanders (FWO), Sophia Children's Hospital Foundation (SSWO), Stichting Agis Zorginnovatie, Erasmus Trustfonds, and European Society for Parenteral and Enteral Nutrition (ESPEN) research grant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(124 citation statements)
references
References 22 publications
(23 reference statements)
2
116
3
Order By: Relevance
“…14.1: Withholding parenteral nutrition for up to one week can be considered in critically ill term neonates and children, independent of nutritional status, while providing micronutrients B Consensus [8,9,22,[25][26][27]156] In critically ill children, does the use of a feeding protocols impact on clinical outcomes? 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14.1: Withholding parenteral nutrition for up to one week can be considered in critically ill term neonates and children, independent of nutritional status, while providing micronutrients B Consensus [8,9,22,[25][26][27]156] In critically ill children, does the use of a feeding protocols impact on clinical outcomes? 15…”
Section: Discussionmentioning
confidence: 99%
“…The post-pyloric or small intestinal site for EN may be used in patients unable to tolerate gastric feeding or those at high risk for aspiration. Existing data are insufficient to make recommendations regarding the use of continuous vs intermittent gastric feeding R11.2: Gastric feeding is not inferior to post pyloric feeding in the majority of critically ill children outcome in critically ill children [26,27]. Despite the lack of effect shown of protocols on mortality and NEC in the meta-analysis, as the level of this evidence was low, all individual studies did show positive effect on other variables such as time to initiate feeding and achievement of energy goals, but it was not possible to pool these in a meta-analysis.…”
Section: Q8 What Is the Role Of Immunonutrition In Critically Ill Chmentioning
confidence: 99%
“…Secondary analyses of the PEPaNIC trial showed that withholding PN was also beneficial in term neonates and children who were undernourished at admission [373,374], although withholding parenteral nutrition in term neonates was also associated with increased risk of severe hypoglycemia [373]. A long-term follow-up 2 years after PICU admission showed that withholding parenteral nutrition for 1 week did not affect survival, anthropometrics, or health status, but did improve certain domains of neurocognitive development [375]. Although the results of the PEP-aNIC trial corroborated the findings from adult RCTs, the optimal timing of parenteral nutrition in the critically ill child with sepsis is still not clear [371,[376][377][378].…”
mentioning
confidence: 99%
“…Furthermore, the concerns on the efficacy and safety of stopping the intervention (in our case withholding PN) should be addressed if possible. Since the launch of this survey, several secondary analyses have investigated the main concerns, such as the harm associated with administration of amino acids [29], the efficacy and safety of withholding PN in undernourished children [21] and neonates [20], the long-term effects on physical and neuropsychological functions [30], and the cost-effectiveness of withholding PN [31]. All these new findings were supportive for de-implementation of early-PN.…”
Section: Discussionmentioning
confidence: 95%